The dose-response relationship of subretinal gene therapy with rAAV2tYF-CB-hRS1 in a mouse model of X-linked retinoschisis - Hassan, Salma; Hsu, Ying; Thompson, Jacob M.; Kalmanek, Emily; VandeLune, Joel A.; Stanley, Sarah; Drack, Arlene V. (Frontiers in Medicine, 2024)
We respectfully re-submit our manuscript entitled "A dose response study of subretinal gene therapy in a mouse model of X-linked retinoschisis" to Frontiers in Medicine -Ophthalmology for consideration. In our research, our primary objective was to explore an alternative route of delivery for the rAAV2tYF-CB-hRS1 gene therapy vector, specifically through subretinal administration. We conducted this study in a mouse model of X-linked retinoschisis with the aim of assessing its dose-response characteristics. Our motivation for pursuing this research stemmed from the lack of improvements in the phenotype during a clinical trial (NCT02416622) when administering this vector intravitreally as it also caused immune responses at higher doses. We believe that our study, with its alternative route of delivery, could yield promising outcomes.We identified that the medium dose (8E8 vg/eye) exhibited remarkable long-term restoration of the conespecific pathway, short-term preservation of the rod-specific pathway, a reduction in cyst severity, and improvements in a trend toward functional vision improvement on a visually guided swim assay. Our study also uncovered a previously undocumented phenomenon in the mouse model of X-linked retinoschisis; we demonstrated a hyper-normal a-wave response during dark-adapted dim flash (0.01 cd•sec/m 2 ) ERG protocol. After the gene therapy delivery, this effect was normalized, highlighting the potential therapeutic impact of our approach.We believe that the significance of our findings extends beyond the realm of preclinical research. The implications of our study suggest that the subretinal route of vector administration may hold promise for clinical trials in humans. Given the significance of our findings, we are excited to share them with the readership of Frontiers in Medicine -Ophthalmology, specifically the issue dedicated to X-linked Retinoschisis: Mechanisms and Therapies. We believe that this research will be of considerable interest to those interested in understanding the impact of alternative delivery routes for the AAV2tYF-CB-hRS1 gene therapy vector. It aligns with the theme of exploring innovative therapeutic approaches for this condition.